Checkpoint Inhibitors The Diagnosis and Treatment of Side Effects - Heinzerling, Lucie; De Toni, Enrico N.; Schett, Georg; Hundorfean, Gheorghe; Zimmer, Lisa (Deutsches Ärzteblatt international, 2019)
Background: Treatment with checkpoint inhibitors such as anti-programmed death-1 (anti-PD-1), anti-PD-ligand 1 (anti-PD-L1), and anti-cytotoxic T-Iymphocyte antigen-4 (anti-CTLA-4) antibodies can prolong the survival of cancer patients, but it also induces autoimmune side effects in 86-96% of patients by activating the immune system. In 17-59% of patients, these are severe or even life-threatening.
CRIS-Team WoS Importer:2019-04-12